A cobalt-doped manganese-based catalyst and its preparation and application
Through cobalt doping, the preparation method of manganese-based catalyst is improved, and the problems of inactivation, low density and poor cycle stability in the presence of water are solved, and the preparation of high-performance catalysts is realized, which is suitable for the industrial production of methacrylonitrile.
Patent Information
- Application Number
- CN202111352744.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-11-16
AI Technical Summary
The existing manganese-based catalysts are inactivated in the presence of water, have low density, are complex in subsequent recycling and utilization of reactions, and have low utilization of active components, making it difficult to meet the industrial production needs of methacrylonitrile.
The preparation method of manganese-based oxide catalyst and supported catalyst is improved by cobalt doping, and the water resistance, density and cycle stability of the catalyst are improved, and high-performance cobalt-doped manganese-based oxide catalyst and supported catalyst are prepared.
It achieves high water resistance, increased density and good cycle stability of the catalyst, improves the yield and selectivity of methacrylonitrile, is suitable for various production environments, and has great industrial application value.
Smart Images

Figure BDA0003356458060000081 
Figure BDA0003356458060000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of improved catalyst preparation, and in particular to a preparation method and application of a cobalt-doped manganese-based catalyst for producing methacrylonitrile in a liquid phase. Background Art
[0002] Methacrylonitrile (MAN) is the main monomer of polymethacrylimide (PMI) foam plastics. PMI foam plastics have excellent mechanical properties, heat resistance temperature up to 240°C, easy processing and molding, and are ideal core materials for sandwich structure composite materials. Traditional foam plastics such as polyvinyl chloride, cross-linked polyvinyl chloride, polyurethane, etc., which are used as core materials, will have their strength greatly reduced and deformed when the temperature reaches above 130°C. They can no longer meet the requirements of high-end fields such as aerospace, military, and civil for the strength, stiffness, and temperature of core materials. At present, there is no commercialized PMI foam plastic in China, but the demand for it in the aviation and civil fields is increasing, and it can only rely on imports to meet this demand.
[0003] Domestic research in this field is still in the experimental stage. At present, the source of methacrylonitrile is limited by the monopoly of international companies, there are few channels for importing methacrylonitrile, and the price is expensive. Domestic production can only be carried out in small batches in laboratories. Therefore, the realization of mass production of methacrylonitrile is a prerequisite for realizing the engineering of domestic PMI foam, reducing the cost of PMI foam plastics, and expanding the application field of domestic PMI foam plastics. At the same time, China's industrial processes such as petroleum cracking and FCC (fluid catalytic cracking) produce a large amount of isobutylene. As the application of MTBE is restricted, the development of technology for the high value-added utilization of isobutylene is particularly necessary. In addition to the production of polyisobutylene (PIB) and the superposition of high-octane gasoline, the production of methacrylonitrile is also one of the very important high value-added utilization routes of isobutylene.
[0004] At present, methacrylonitrile is generally obtained as a by-product of synthetic acrylonitrile. Asahi Chemical Co., Ltd. of Japan has developed the technology of producing MAN by isobutylene method, and Sohio Company of the United States has realized the industrial production of pure isobutylene ammoxidation to produce methacrylonitrile, while the industrialization in this regard is still blank in China. The direct ammoxidation of isobutylene to prepare methacrylonitrile mostly adopts Mo-Bi-Fe catalyst similar to the ammoxidation of propylene, such as the following patent reports CN 99119905.7, CN200510046593.6, US462202, CN91100078.X, etc. The reaction is a highly exothermic reaction with a reaction temperature of 400-500°C. In addition to the main reaction, there are a series of side reactions, and the main by-products include hydrocyanic acid, acetonitrile, acrylonitrile, methacrolein, carbon monoxide and carbon dioxide. In addition to the Mo-Bi-Fe catalysts, the research on the direct use of Mo-V catalysts for the direct ammoxidation of isobutane to prepare methacrylonitrile (CN200510046593.6, CN 99806538.2) is also reported in patents. This system also has the disadvantage of producing a large amount of by-products. In addition to the above catalyst systems, Patent 201910968710.6 reports a manganese-based catalyst for synthesizing methacrylonitrile and its preparation method and application, but the manganese catalyst in this system has the following problems: 1) Water is generated during the ammoxidation of methacrolein, and the catalyst has poor water resistance. The catalyst will quickly deactivate in the presence of water and its activity is irreversible. 2) Catalyst 0.2-0.3g / cm 3 The density is low, and a large amount of solvent needs to be added during the reaction to ensure uniform mass transfer, resulting in a low product concentration in the reaction solution and high subsequent separation energy consumption. 3) The effective utilization rate of the active component manganese is low.
[0005] The present invention still adopts the two-step isobutylene process route for preparing methacrylonitrile. The first step is to obtain methacrolein by catalytic oxidation from isobutylene; the second step is the liquid phase ammoxidation process involved in the present invention, in which methacrolein is catalytically ammoxidized under liquid phase conditions to obtain methacrylonitrile. Compared with the traditional one-step gas phase method, the key process route involved in the two-step method is liquid phase and low temperature reaction; the operation is simple, the side reaction is less (no hydrocyanic acid is produced), and the high energy consumption of high temperature reaction and the potential danger caused by the byproduct hydrocyanic acid are avoided. At the same time, in order to solve the shortcomings of the existing manganese-based catalyst, the present invention successfully prepares cobalt-doped manganese-based oxide catalysts and cobalt-doped manganese-based supported catalysts with excellent performance by improving the catalyst preparation method and adjusting the active components.
[0006] Compared with the existing technology, the cobalt-doped manganese-based oxide catalyst of the present invention has the advantages of good water resistance, high density, good cycle stability and the like; on this basis, the designed cobalt-doped manganese-based supported catalyst has the advantages of good water resistance, high density, wear resistance, high utilization rate of active components, good cycle stability and the like, can be applied to various production environments, has great industrial application value, fills the domestic research gap in this field, and lays a solid foundation for the industrialization of methacrylonitrile.
[0007] Purpose of the Invention
[0008] In view of the prior art, the purpose of the present invention is to provide a preparation method and application of a cobalt-doped manganese-based catalyst for producing methacrylonitrile. The catalyst can solve the shortcomings of the existing manganese-based catalyst, and the preparation method is simple, the cost is low, and it has good activity and stability.
[0009] The present invention is achieved through the following technical solutions:
[0010] A method for preparing a cobalt-doped manganese-based catalyst, characterized in that it is one or more of a cobalt-doped manganese-based oxide catalyst or a cobalt-doped manganese-based supported catalyst;
[0011] Preparation of Cobalt-doped Manganese-based Oxide Catalysts:
[0012] 1) Weigh potassium permanganate and deionized water, mix them, stir them at room temperature for 1 min-4 h to fully dissolve them, and obtain a potassium permanganate aqueous solution with a mass concentration range of 1-6%. Add an alkaline compound or an aqueous solution of an alkaline compound to the solution, adjust the pH range of the aqueous solution to 8-12, and stir the mixed solution for 10 min-6 h to obtain solution A;
[0013] 2) weighing manganese salt and cobalt salt, adding deionized water, stirring and dissolving at room temperature to obtain solution B, wherein the mass concentration of manganese is in the range of 2-50%; and the molar ratio of manganese to cobalt is 1:0.01-0.5;
[0014] 3) adding the obtained solution B dropwise into solution A and stirring at room temperature for 1-24 hours; placing the mixture into a crystallization kettle for crystallization at 100-180° C. for 6-24 hours, washing and drying the obtained solid, and calcining at high temperature to obtain a cobalt-doped manganese-based oxide catalyst; wherein the molar ratio of potassium permanganate to manganese is 1:1.0-2.0;
[0015] Preparation of Cobalt-doped Manganese-based Supported Catalysts:
[0016] 1|) Weigh potassium permanganate and deionized water, mix them, stir them at room temperature for 1 min-4 h to fully dissolve them, and obtain a potassium permanganate aqueous solution with a mass concentration range of 1-6%, add a metal oxide carrier containing silicon and aluminum to the solution, add an alkaline compound or an aqueous solution of an alkaline compound to the solution, adjust the pH range of the obtained mixture aqueous solution to 8-12, and stir the mixture for 10 min-6 h to obtain solution A;
[0017] 2) weighing manganese salt and cobalt salt, adding deionized water, stirring and dissolving at room temperature to obtain solution B, wherein the mass concentration of manganese is in the range of 2-50%; and the molar ratio of manganese to cobalt is 1:0.01-0.5;
[0018] 3) Add the obtained solution B dropwise into solution A and stir at room temperature for 1-24 hours; put the mixture into a crystallization kettle for crystallization at 100-180°C for 6-24 hours, wash and dry the obtained solid, and calcine at high temperature to obtain a cobalt-doped manganese-based oxide catalyst. The mass percentage of manganese in the obtained cobalt-doped manganese-based supported catalyst is 0.2-20%, wherein the molar ratio of potassium permanganate to manganese is 1:1.0-2.0;
[0019] The cobalt salt and manganese salt are one or more of the nitrates, acetates and sulfates of the corresponding metals.
[0020] In the preparation method of the above cobalt-doped manganese-based catalyst, the carrier is a metal oxide composite carrier containing silicon and aluminum, which is a composition formed by silicon dioxide, aluminum oxide and other metal oxides, and the other metal oxides are selected from alkali metal oxides, alkaline earth metal oxides, TiO 2 、ZrO 2 , spinel, hydrotalcite, one or more thereof;
[0021] The mass content of silicon dioxide is 30%-90%, preferably 45%-80%; the mass content of aluminum oxide is 8%-65%, preferably 15%-55%.
[0022] In the carrier component, the precursor of silicon dioxide is one or more of various forms of silica sol, silica gel, silicon spheres, and white carbon black; the precursor of aluminum oxide is one or more of aluminum nitrate, aluminum chloride, aluminum hydroxide, aluminum phosphate, aluminum sulfate, and aluminum oxide powder; the other metal precursors are one or more of nitrates, oxides, hydroxides, compounds, or complexes of the corresponding metals;
[0023] In the preparation method of the above-mentioned cobalt-doped manganese-based catalyst, the preparation process of the carrier is: under stirring conditions, the silica precursor, the alumina precursor and other metal precursors are fully mixed, and then an acid is added to adjust the pH of the mixed solution to 0.5-2.5, and the mixture is kept at 30-60°C. After stirring and aging for 1-48 hours, a mixture is obtained. After the mixture is spray-dried and formed, spherical particles of 10-200 μm are obtained, and the metal oxide composite carrier is obtained after calcination in air and an inert atmosphere.
[0024] In the preparation method of the above cobalt-doped manganese-based catalyst, the crystallization temperature is 100-180°C (preferably 120-140°C), and the crystallization time is 6-24h (preferably 12-16h).
[0025] In the preparation method of the above cobalt-doped manganese-based catalyst, the alkaline compound is one or more of sodium hydroxide, potassium hydroxide, cesium carbonate, potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate, urea, ammonia gas and ammonia water, preferably ammonia water and / or urea aqueous solution with a mass concentration of 25-28%; the mass concentration of the alkaline compound aqueous solution is 0.1-50%, preferably 10-30%. In the preparation method of the above cobalt-doped manganese-based catalyst, the catalyst precursor is dried in a vacuum programmed temperature drying method; dried at 30-80°C (preferably 50-80°C) for 0.5-4h under a vacuum degree of 1-20mmHg, and then heated to 100-150°C (preferably 120°C) and dried for 0.5-4h;
[0026] The catalyst precursor is calcined at a temperature of 200-500° C. (preferably 300-400° C.) and a calcination time of 2-10 h (preferably 3-6 h).
[0027] The catalyst was obtained by adopting the above preparation method.
[0028] A method for producing methacrylonitrile using one or more of the catalysts obtained by the above preparation method,
[0029] In the presence of a cobalt-doped manganese-based catalyst and an organic solvent, oxygen and / or air are used as an oxidant, an ammonia source is added, and
[0030] Methacrolein is used as a raw material, and the product methacrylonitrile is obtained through an ammoxidation reaction; the reaction temperature is -30 to 80°C (preferably 0 to 10°C), and the reaction time is 2 to 60 minutes (preferably 10 to 20 minutes);
[0031] The cobalt-doped manganese-based catalyst includes one or more of a cobalt-doped manganese-based oxide catalyst or a cobalt-doped manganese-based supported catalyst, and can catalyze the ammoxidation of methacrolein to prepare methacrylonitrile.
[0032] In the above-mentioned preparation method of methacrylonitrile, the reaction solvent is one or a mixture of toluene, ethylbenzene, xylene (o, m, para), trimethylbenzene (meta, iso), acetonitrile, propionitrile, butyronitrile, acetone, ethyl acetate, butyl acetate, hexyl acetate, 1,4-dioxane, ethylene glycol dimethyl ether, and diethylene glycol dimethyl ether.
[0033] The ammonia source is one or a mixture of ammonia gas, ammonia water, ammonium chloride, ammonium acetate, ammonium oxalate and urea.
[0034] In the above-mentioned method for producing methacrylonitrile, the molar ratio of the methacrolein to the manganese element in the catalyst is: 1:0.001-5, preferably 1:0.05-0.5; the molar ratio of the methacrolein to oxygen is: 1:1-18, preferably 1:2-3; the molar ratio of the methacrolein to the ammonia source is: 1:1-40, preferably 1:3-4.
[0035] The density of the cobalt-doped manganese-based oxide catalyst is 0.4-0.7 g / cm 3 ,
[0036] The density of the cobalt-doped manganese-based supported catalyst is in the range of 0.7-1.2 g / cm 3 .
[0037] The invention obtains a cobalt-doped manganese-based oxide catalyst with high density and high water resistance by a hydrothermal co-doping method; the cobalt-doped manganese-based oxide catalyst of the invention is used for the reaction of preparing methacrylonitrile by ammoxidation, which solves the problems of poor water resistance, low density, and complicated subsequent recycling of the previous manganese-based catalysts; the cobalt-doped manganese-based supported catalyst further improves the performance of the catalyst, has the advantages of wear resistance, high utilization rate of active components, easy separation, etc., is suitable for various production environments, and has great industrial application value.
[0038] Advantages of the present invention:
[0039] The invention relates to a liquid phase ammoxidation process involved in the second step of the process route of preparing methacrylonitrile by a two-step process of isobutylene, wherein methacrylaldehyde is subjected to catalytic ammoxidation under liquid phase conditions to obtain methacrylonitrile. Compared with the conventional one-step gas phase process, the key process route involved in the two-step process is liquid phase and low temperature reaction; the operation is simple, the side reaction is less (no hydrocyanic acid is produced), and the high energy consumption of high temperature reaction and the potential danger caused by the byproduct hydrocyanic acid are avoided.
[0040] At the same time, Patent 201910968710.6 reported a manganese-based catalyst for synthesizing methacrylonitrile, its preparation method and application, but the manganese catalyst in this system has the following problems: 1) Water is generated during the ammoxidation of methacrolein, and the catalyst has poor water resistance. The catalyst will be rapidly deactivated in the presence of water, and its activity is irreversible. 2) The catalyst is 0.2-0.3g / cm 3 The density is low, and a large amount of solvent needs to be added during the reaction to ensure uniform mass transfer, resulting in a low product concentration in the reaction solution and high subsequent separation energy consumption. 3) The effective utilization rate of the active component manganese is low.
[0041] In order to solve the shortcomings of the existing manganese-based catalysts, the present invention successfully prepares a cobalt-doped manganese-based oxide catalyst and a cobalt-doped manganese-based supported catalyst with excellent performance by improving the catalyst preparation method and adjusting the active components. In the presence of the two cobalt-doped manganese-based catalysts, methacrylonitrile is obtained by ammoxidation reaction, and the yield can reach 95%. Among them, the cobalt-doped manganese-based supported catalyst is subjected to 20 laboratory intermittent reaction cycles, and the catalyst activity remains basically unchanged.
[0042] Compared with the prior art, the cobalt-doped manganese-based oxide catalyst of the present invention has the advantages of good water resistance, high density, good cycle stability, etc.; the cobalt-doped manganese-based supported catalyst has the advantages of good water resistance, high density, wear resistance, high utilization rate of active components, good cycle stability, etc., can be applied to various production environments, has great industrial application value, fills the domestic research gap in this field, and lays a solid foundation for the industrialization of methacrylonitrile. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with specific implementation methods. The protection scope of the present invention includes but is not limited to the following embodiments. Any modifications made to the details and forms of the technical solution of the present invention without departing from the meaning and scope of the present application shall fall within the protection scope of the present invention.
[0044] Example 1
[0045] Weigh 1.8g potassium permanganate and add it to 50mL deionized water, stir at room temperature for 1h until it is completely dissolved, directly add 5g urea aqueous solution (mass concentration 40%), and stir at room temperature for 2h. Weigh 5.4g manganese nitrate aqueous solution (mass concentration 50%) and 2.2g cobalt nitrate hexahydrate and add them to 25mL water, slowly add the obtained aqueous solution to the above potassium permanganate aqueous solution within 30min, continue stirring at room temperature for 12h, put the mixture into a crystallization kettle, crystallize at 120℃ for 12h, cool and open the kettle, pour off the upper mother liquor, wash the obtained solid with water and methanol in turn, then dry at 50℃ for 2h under a vacuum of 2mmHg, then heat to 120℃ and dry for 2h, and the obtained solid A is roasted at 400℃ in air atmosphere for 3h.
[0046] The obtained cobalt-doped manganese-based oxide catalyst A (Mn 3.5 CoO y ) has a density of 0.40 g / cm 3 .
[0047] Example 2
[0048] 100g 30% silica sol (pH = 4.5), 75.026g aluminum nitrate nine hydrate, 8.748g magnesium hydroxide and 20g 75% concentrated nitric acid, 500mL deionized water, mixed at 50°C, kept stirring for 24h, obtained a uniform solid solution suspension, stirred and cooled to room temperature and then spray dried. Spray conditions: 8ml / min feed rate, drying tower temperature 260-280°C, outlet temperature 110-130°C, obtained a spherical powder with a particle size of 58μm. The solid powder was placed in a tubular furnace and calcined under nitrogen with a programmed temperature rise, 30-300°C for 3h (heating rate 1.5°C / min), maintained at 300°C for 4h, 300-600°C for 3h (heating rate 1.7°C / min), maintained at 600°C for 4h. After natural cooling, Si-Mg-Al metal composite oxide carrier a was obtained.
[0049] Weigh 1.8g potassium permanganate and add it to 50mL deionized water, stir at room temperature for 1h until it is completely dissolved, directly add 5g urea aqueous solution (mass concentration 40%) and 42g Si-Mg-Al metal composite oxide carrier, and stir at room temperature for 2h. Weigh 5.4g manganese nitrate aqueous solution (mass concentration 50%) and 2.2g cobalt nitrate hexahydrate and add them to 25mL water. The obtained aqueous solution is slowly added to the above potassium permanganate aqueous solution within 30min, and continued to stir at room temperature for 12h. The mixture is placed in a crystallization kettle and crystallized at 120℃ for 12h. The kettle is cooled and opened, and the upper mother liquor is poured off. The obtained solid is washed with water and methanol in turn, and then dried at 50℃ for 2h under a vacuum of 2mmHg, and then heated to 120℃ and dried for 2h. The obtained solid B is calcined at 400℃ air atmosphere for 3h. The obtained cobalt-doped manganese-based supported catalyst B (3.2wt.%Mn---Mn 3.5 CoO y @Si-Mg-Al-a) has a density of 1.01 g / cm 3 .
[0050] Example 3
[0051] 100g 30% silica sol (pH = 4.5), 75.026g aluminum nitrate nine hydrate, 22.2465g magnesium nitrate and 20g 75% concentrated nitric acid, 500mL deionized water, mixed at 50°C, kept stirring for 24h, obtained a uniform solid solution suspension, stirred and cooled to room temperature and then spray dried. Spray conditions: 6ml / min feed rate, drying tower temperature 260-280°C, outlet temperature 110-130°C, obtained spherical powder with a particle size of 41μm. The solid powder was placed in a tubular furnace and calcined under nitrogen or air with a programmed temperature rise, 30-300°C for 3h (heating rate 1.5°C / min), maintained at 300°C for 4h, 300-600°C for 3h (heating rate 1.7°C / min), maintained at 600°C for 4h. After natural cooling, Si-Mg-Al metal composite oxide carrier b was obtained.
[0052] Weigh 1.7g potassium permanganate and add it to 50mL deionized water, stir at room temperature for 1h until it is completely dissolved, directly add 18.5g ammonia aqueous solution (mass concentration 25%) and 42g Si-Mg-Al metal composite oxide carrier, and stir at room temperature for 2h. Weigh 5.4g manganese nitrate aqueous solution (mass concentration 50%) and 1.2g cobalt nitrate hexahydrate and add them to 25mL water, slowly add the obtained aqueous solution to the above potassium permanganate aqueous solution within 30min, continue stirring at room temperature for 12h, put the mixture into a crystallization kettle, crystallize at 120℃ for 12h, cool and open the kettle, pour off the upper mother liquor, wash the obtained solid with water and methanol in turn, then dry at 50℃ for 2h under a vacuum of 2mmHg, then heat to 120℃ and dry for 2h, and the obtained solid C is roasted at 400℃ air atmosphere for 3h.
[0053] The obtained cobalt-doped manganese-based supported catalyst C (3.2wt.% Mn---Mn 6.3 CoO y @Si-Mg-Al-b) has a density of 0.85 g / cm 3 .
[0054] Example 4
[0055] Si-Mg-Al metal composite oxide support (see Example 3).
[0056] Weigh 1.7g potassium permanganate and add it to 50mL deionized water, stir at room temperature for 1h until it is completely dissolved, directly add 18.5g ammonia aqueous solution (mass concentration 25%) and 80g Si-Mg-Al metal composite oxide carrier, and stir at room temperature for 2h. Weigh 5.4g manganese nitrate aqueous solution (mass concentration 50%) and 1.2g cobalt nitrate and add them to 25mL water, slowly add the obtained aqueous solution to the above potassium permanganate aqueous solution within 30min, continue stirring at room temperature for 12h, put the mixture into a crystallization kettle, crystallize at 120℃ for 12h, cool and open the kettle, pour off the upper mother liquor, wash the obtained solid with water and methanol in turn, then dry at 50℃ for 2h under a vacuum of 2mmHg, then heat to 130℃ and dry for 2h, and the obtained solid D is roasted at 400℃ in air atmosphere for 3h.
[0057] The obtained cobalt-doped manganese-based supported catalyst D (1.7wt.%Mn---Mn 6.3 CoO y @Si-Mg-Al-b) has a density of 0.95 g / cm 3 .
[0058] Example 5
[0059] Si-Mg-Al metal composite oxide support (see Example 3).
[0060] Weigh 0.85g potassium permanganate and add it to 50mL deionized water, stir at room temperature for 1h until it is completely dissolved, directly add 18.5g ammonia aqueous solution (mass concentration 25%) and 80g Si-Mg-Al metal composite oxide carrier, and stir at room temperature for 2h. Weigh 2.7g manganese nitrate aqueous solution (mass concentration 50%) and 0.6g cobalt nitrate and add them to 25mL water, slowly add the obtained aqueous solution to the above potassium permanganate aqueous solution within 30min, continue stirring at room temperature for 12h, put the mixture into a crystallization kettle, crystallize at 120℃ for 12h, cool and open the kettle, pour off the upper mother liquor, wash the obtained solid with water and methanol in turn, then dry at 50℃ for 2h under a vacuum of 2mmHg, then heat to 120℃ and dry for 2h, and the obtained solid E is roasted at 400℃ in air atmosphere for 5h.
[0061] The obtained cobalt-doped manganese-based supported catalyst E (0.87wt.%Mn---Mn 6.3 CoO y @Si-Mg-Al-b) has a density of 0.97 g / cm 3 .
[0062] Example 6
[0063] Si-Mg-Al metal composite oxide support (see Example 3).
[0064] Weigh 1.7g potassium permanganate and add it to 50mL deionized water, stir at room temperature for 1h until it is completely dissolved, directly add 7.5g potassium hydroxide aqueous solution (mass concentration 25%) and 80g Si-Mg-Al metal composite oxide carrier, and stir at room temperature for 2h. Weigh 5.4g manganese nitrate aqueous solution (mass concentration 50%) and 0.6g cobalt nitrate and add them to 25mL water, slowly add the obtained aqueous solution to the above potassium permanganate aqueous solution within 30min, continue stirring at room temperature for 12h, put the mixture into a crystallization kettle, crystallize at 150℃ for 24h, cool and open the kettle, pour off the upper mother liquor, wash the obtained solid with water and methanol in turn, then dry at 50℃ for 2h under a vacuum of 2mmHg, then heat to 120℃ and dry for 2h, and the obtained solid F is roasted at 400℃ in air atmosphere for 5h.
[0065] The obtained cobalt-doped manganese-based supported catalyst F (1.7wt.%Mn---Mn 12.5 CoO y @Si-Mg-Al-b) has a density of 0.96 g / cm 3 .
[0066] Comparative Example 1
[0067] Weigh 1.8g potassium permanganate and add it to 50mL deionized water, stir at room temperature for 1h until it is completely dissolved, directly add 5g urea aqueous solution (mass concentration 40%), and stir at room temperature for 2h. Weigh 5.4g manganese nitrate aqueous solution (mass concentration 50%) and add it to 25ml water. The obtained aqueous solution is slowly added to the above potassium permanganate aqueous solution within 30min, and continued to stir at room temperature for 12h. The mixture is placed in a crystallization kettle and crystallized at 120℃ for 12h. Cool the kettle and pour off the upper mother liquor. The obtained solid is washed with water and methanol in turn, and then dried at 50℃ for 2h under a vacuum of 2mmHg, and then heated to 120℃ and dried for 2h. The obtained solid G is roasted at 400℃ in air atmosphere for 3h.
[0068] The obtained manganese-based catalyst G(MnO 2 ) has a density of 0.25 g / cm 3 .
[0069] Comparative Example 2
[0070] 100g 30% silica sol (pH = 4.5), 75.026g aluminum nitrate nine hydrate, 8.748g magnesium hydroxide and 20g 75% concentrated nitric acid, 500mL deionized water, mixed at 50°C, kept stirring for 24h, obtained a uniform solid solution suspension, stirred and cooled to room temperature and then spray dried. Spray conditions: 8mL / min feed rate, drying tower temperature 260-280°C, outlet temperature 110-130°C, obtained spherical powder with a particle size of 58μm. The solid powder was placed in a tubular furnace and calcined under nitrogen or air with a programmed temperature rise, 30-300°C for 3h (heating rate 1.5°C / min), maintained at 300°C for 4h, 300-600°C for 3h (heating rate 1.7°C / min), maintained at 600°C for 4h. After natural cooling, Si-Mg-Al metal composite oxide carrier a was obtained.
[0071] Weigh 1.8g potassium permanganate and add it to 50mL deionized water, stir at room temperature for 1h until it is completely dissolved, directly add 5g urea aqueous solution (mass concentration 40%) and 42g Si-Mg-Al metal composite oxide carrier, and stir at room temperature for 2h. Weigh 5.4g manganese nitrate aqueous solution (mass concentration 50%) and add it to 25mL water, slowly add the obtained aqueous solution to the above potassium permanganate aqueous solution within 30min, continue stirring at room temperature for 12h, put the mixture into a crystallization kettle, crystallize at 120℃ for 12h, cool and open the kettle to pour off the upper mother liquor, wash the obtained solid with water and methanol in turn, then dry at 50℃ for 2h under a vacuum of 2mmHg, then heat to 120℃ and dry for 2h, and the obtained solid H is calcined at 400℃ air atmosphere for 3h.
[0072] The obtained manganese-based catalyst H (3.2wt.%Mn---MnO 2 @Si-Mg-Al-a) has a density of 0.92 g / cm 3 .
[0073] Example 7
[0074] A cobalt-doped manganese-based catalyst (the molar ratio of methacrolein to manganese in the catalyst is 1:0.02), 0.1 g of methacrolein, and 4 mL of butyl acetate were sequentially added into a 25 mL stainless steel reactor with a polytetrafluoroethylene liner. The reactor was sealed and filled with 0.5 MPa ammonia (0.3 g) first, and then with oxygen (0.5 g). The total pressure was about 1.0 MPa. The reaction was carried out in a 0°C water bath for 20 min. After the reaction was completed, the reactor was cooled with an ice-water bath, and the air was slowly released to normal pressure. The reactor was opened, an internal standard was added to the reaction solution, and the conversion rate and yield were analyzed by gas chromatography.
[0075] Comparison of the catalysts used in the above examples
[0076]
[0077]
[0078] Compared with the catalyst G (MnO 2 ) Compared with the above, the density of cobalt-doped manganese-based oxide catalyst A and cobalt-doped manganese-based supported catalyst BF increased to varying degrees. This changed the problem of low density of manganese catalyst reported in patent 201910968710.6 (0.2-0.3 g / cm 3 ), in the case of less solvent, the mass transfer of the reaction liquid is more complete, reducing the subsequent separation energy consumption. Compared with Comparative Example 1, the improvement of the catalyst used in Examples 1-6 and Comparative Example 2 reduces the loading amount of the active component manganese and improves the effective utilization rate of active manganese.
[0079] Comparison of the results of using the above prepared catalysts for the synthesis of methacrylonitrile
[0080]
[0081] Table c: indicates the experimental results of the catalyst being used twice without treatment. 2 ) During the ammoxidation of methacrolein, the activity of the catalyst decreased rapidly under the action of water, indicating that the catalyst has poor water resistance.
[0082] Compared with Comparative Example 1, the manganese-based oxide catalyst A used in Example 1 was cobalt-doped to improve the water resistance of the catalyst. After 20 cycles, the yield and selectivity of methacrylonitrile remained basically stable. Compared with Comparative Example 1, the supported catalyst H used in Comparative Example 2 improved the wear resistance of the catalyst after MnO2 was supported on a Si-Mg-Al metal composite oxide support. The yield and selectivity of methacrylonitrile decreased slightly after 20 cycles. Catalyst BF was further obtained by using the loading and cobalt-doping methods. It was found that the catalyst activity remained basically unchanged after 20 cycles of laboratory intermittent reaction.
[0083] Compared with the existing technology, the cobalt-doped manganese-based oxide catalyst of the present invention has the advantages of good water resistance, high density, good cycle stability, etc.; the cobalt-doped manganese-based supported catalyst has the advantages of good water resistance, high density, wear resistance, high utilization rate of active components, good cycle stability, etc., can be applied to various production environments, has great industrial application value, and fills the domestic research gap in this field.
Claims
1. A method for preparing a cobalt-doped manganese-based catalyst, characterized in that: It is a cobalt-doped manganese-based supported catalyst; Preparation of cobalt-doped manganese-based supported catalyst: 1) Weigh potassium permanganate and deionized water, mix them, stir them at room temperature for 1 min-4 h to fully dissolve them, and obtain a potassium permanganate aqueous solution with a mass concentration range of 1-6%. Add a metal oxide carrier containing silicon and aluminum to the above potassium permanganate aqueous solution, and then add an alkaline compound or an aqueous solution of an alkaline compound to the solution. Adjust the pH value of the obtained mixture aqueous solution to 8-12, and stir the mixture for 10 min-6 h to obtain solution A; 2) Weigh manganese salt and cobalt salt, add deionized water, stir and dissolve at room temperature to obtain solution B, wherein the mass concentration of manganese is in the range of 2-50%; the molar ratio of manganese to cobalt is 1:0.01-0.5; 3) adding the obtained solution B dropwise into the solution A and stirring at room temperature for 1-24 hours; placing the mixture into a crystallization kettle for crystallization at 100-180° C. for 6-24 hours, washing and drying the obtained solid, and calcining at high temperature to obtain a cobalt-doped manganese-based supported catalyst, wherein the mass percentage of manganese in the obtained cobalt-doped manganese-based supported catalyst is 0.2-20%, wherein the molar ratio of potassium permanganate to manganese is 1:1.0 ~2.0; The cobalt salt and manganese salt are one or more of the nitrate, acetate and sulfate of the corresponding metal respectively; The carrier is a metal oxide composite carrier containing silicon and aluminum, which is a composition formed by silicon dioxide, aluminum oxide and other metal oxides, and the other metal oxides are selected from alkaline earth metal oxides; The mass content of silicon dioxide is 30%-90%; the mass content of aluminum oxide is 8%-65%; In the carrier component, the precursor of silicon dioxide is one or more of various forms of silica sol, silica gel, silicon spheres, and white carbon black; the precursor of aluminum oxide is one or more of aluminum nitrate, aluminum chloride, aluminum hydroxide, aluminum phosphate, aluminum sulfate, and aluminum oxide powder; the precursor of other metal oxides is one or more of nitrates, oxides, and hydroxides of corresponding metals; The preparation process of the carrier is as follows: under stirring conditions, a silica precursor, an alumina precursor and other metal oxide precursors are fully mixed, an acid is added to adjust the pH of the mixed solution to 0.5-2.5, the mixture is maintained at 30-60°C, and stirring and aging is continued for 1-48 hours to obtain a mixture, the mixture is spray-dried and formed to obtain spherical particles of 10-200 μm, and the metal oxide composite carrier containing silicon and aluminum is obtained after calcination in air and / or an inert atmosphere.
2. The preparation method according to claim 1, characterized in that: The mass content of silicon dioxide is 45%-80%; the mass content of aluminum oxide is 15%-55%.
3. The preparation method according to claim 1, characterized in that: The crystallization temperature is 120-140°C, and the crystallization time is 12-16h.
4. The preparation method according to claim 1, characterized in that: The alkaline compound is one or more of sodium hydroxide, potassium hydroxide, cesium carbonate, potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate, urea, ammonia gas and ammonia water, and the ammonia water and / or urea are aqueous solutions with a mass concentration of 25-28%; the mass concentration of the aqueous solution of the alkaline compound is 0.1-50%.
5. The preparation method according to claim 4, characterized in that: The mass concentration of the alkaline compound aqueous solution is 10-30%.
6. The preparation method according to claim 1, characterized in that: The drying method of step 3) is a vacuum programmed temperature drying method; drying at 30-80°C for 0.5-4h under a vacuum degree of 1-20 mmHg, and then drying at 100-150°C for 0.5-4h; Step 3) calcination temperature is 200-500°C and calcination time is 2-10h.
7. The preparation method according to claim 6, characterized in that: The drying method of step 3) is a vacuum program heating drying method; drying at 50-80° C. for 0.5-4 h, and then heating to 120° C. for 0.5-4 h; Step 3) The calcination temperature is 300-400°C and the calcination time is 3-6h.
8. A catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. A method for producing methacrylonitrile using the catalyst according to claim 8, In the presence of a cobalt-doped manganese-based catalyst and an organic solvent, oxygen and / or air are used as an oxidant, an ammonia source is added, and methacrolein is used as a raw material to obtain the product methacrylonitrile through an ammonia oxidation reaction; the reaction temperature is 0-10°C and the reaction time is 2-60min; The cobalt-doped manganese-based catalyst is a cobalt-doped manganese-based supported catalyst, which can catalyze the ammoxidation of methacrolein to prepare methacrylonitrile.
10. The method according to claim 9, characterized in that: The reaction time is 10-20 minutes.
11. The method according to claim 9, characterized in that: The reaction solvent is one or a mixture of toluene, ethylbenzene, o-xylene, m-xylene, p-xylene, unsymmetrical trimethylolene, mesitylene, acetonitrile, propionitrile, butyronitrile, acetone, ethyl acetate, butyl acetate, hexyl acetate, 1,4-dioxane, ethylene glycol dimethyl ether, and diethylene glycol dimethyl ether; The ammonia source is one or a mixture of ammonia gas, ammonia water, ammonium chloride, ammonium acetate, ammonium oxalate and urea.
12. The method according to claim 9, characterized in that: The molar ratio of the methacrolein to the manganese element in the catalyst is 1:0.001-5; The molar ratio of the methacrolein to the oxygen is 1:1-18; the molar ratio of the methacrolein to the ammonia source is 1:1-40.
13. The method according to claim 12, characterized in that: The molar ratio of the methacrolein to the manganese element in the catalyst is 1:0.1-0.5; The molar ratio of methacrolein to oxygen is 1:2-3; The molar ratio of the methacrolein to the ammonia source is 1:3-4.
Citation Information
Patent Citations
Load type non-noble metal catalyst as well as preparation and application thereof to synthesis of nitrile
CN106881131A
Manganese-based catalyst for synthesizing methacrylonitrile as well as preparation and application of catalyst
CN112642422A